A Case Series on Cardiac and Skeletal Involvement in Two Families with PRKAG2 Mutations - Anita Sri; Piers Daubeney; Sanjay Prasad; John Baksi; Maria Kinali; Inga Voges (Case Reports in Pediatrics)
Background. PRKAG2 is a rare autosomal dominant syndrome that mainly presents with hypertrophic cardiomyopathy, ventricular preexcitation, and conduction abnormalities. This case report demonstrates that the PRKAG2 mutation presents with various phenotypes already in pediatric patients. Case Summary. We describe the clinical and investigative findings in two families with a PRKAG2 mutation from the different variants in the gene on chromosome 7q36.1, emphasising that the variability of phenotypes and that presentation in childhood is common. Furthermore, we highlight that skeletal myopathy and hypertrophic cardiomyopathy are significant debilitating characteristics of the PRKAG2 mutation. Conclusion. In our report of adult and pediatric patients, early presentation in childhood with hypertrophic cardiomyopathy and skeletal muscle involvement was common, demonstrating the challenges of the clinical management of PRKAG2 mutations.